Concurrent and overlapping surgery: perspectives from surgeons on spinal posterior instrumented fusion for adolescent idiopathic scoliosis. (2021) - Allahabadi, Sachin; Wu, Hao-Hua; Allahabadi, Sameer; Woolridge, Tiana; Kohn, Michael A.; Diab, Mohammad
Abstract: Purpose: The purpose of this study was to determine perspectives of surgeons regarding simultaneous surgery in patients undergoing posterior spine instrumentation and fusion (PSIF) for adolescent idiopathic scoliosis (AIS). Methods: A survey was administered to orthopaedic trainees and faculty regarding simultaneous surgery for primary PSIF for AIS. A five-point Likert scale (1: 'Strongly Disagree' to 5: 'Strongly Agree') was used to assess agreement with statements about simultaneous surgery. We divided simultaneous surgery into concurrent, when critical portions of operations occur at the same time, and overlapping, when noncritical portions occur at the same time. Results: The 72 respondents (78.3% of 92 surveyed) disagreed with concurrent surgery for 'one of my patients' (response mean 1.76 (sd 1.03)) but were more accepting of overlapping surgery (mean 3.94 (sd 0.99); p < 0.0001). The rating difference between concurrent and overlapping surgery was smaller for paediatric and spine surgeons (-1.25) than for residents or those who did not identify a subspecialty (-2.17; p = 0.0246) or other subspecialty surgeons (-2.57; p = 0.0026). Respondents were more likely to agree with explicit informed consent for concurrent surgery compared with overlapping (mean 4.32 (sd 0.91) versus 3.44 (sd 1.14); p < 0.001). Conclusion: Orthopaedic surgeons disagreed with concurrent but were more accepting of overlapping surgery and anaesthesia for PSIF for AIS. Respondents were in greater agreement that patients should be explicitly informed of concurrence than of overlap. The surgical community's evidence and position regarding simultaneous surgery, in particular overlapping, must be more effectively presented to the public in order to bridge the gap in perspectives. Level of Evidence: IV